The Relevance and Necessity of Optimal Use of Antibacterial Drugs in the Prevention of Intestinal Microflora Imbalance - Rustamdjanovna, Nargiza Rakhimova (American Journal of Bioscience and Clinical Integrity, 2025)
The human body, especially the gastrointestinal tract, is home to trillions of microorganisms that have coevolved with the host in a mutually beneficial relationship. Among other things, the gut microbiome's primary job is to ferment indigestible substrates and promote the growth of good bacteria that generate important antimicrobial metabolites like short-chain fatty acids, which stop the growth of harmful bacteria. By use of the colonization resistance mechanism, intestinal microbiota can stop pathogen colonization. Both pathogenic and benign microorganisms have a variety of resistomes. Exposure to both helpful and unfriendly gut microbiomes with antibiotics can cause a resistome response, which impacts colonization resistance. A mechanistic overview of the gut microbiome and how antibiotic therapy affects pathogen colonization and disease is given in the review that follows. Additionally, we go over the colonization and decontamination of multidrug-resistant organisms in the intestine, the epidemiology of immunocompromised people who are at high risk for nosocomial infections, and the direct and indirect mechanisms that control colonization resistance to the pathogens. Because of their ability to combat infections, antibiotics have been a staple of medical care during the past century. In the context of MDA, the effects of antibiotic use on the gut flora are reviewed in this publication. It is now widely known that the gut microbiota plays a crucial role in human metabolism and physiology, and exposure to antibiotics may have a negative effect on host health through unintended consequences for the microbiota and its processes. We also review factors that affect the impact of antibiotic exposure on the microbiota, potential health outcomes of antibiotic-induced microbiota alterations, and strategies that may help alleviate these broader antibiotic-associated microbiota perturbations in order to better understand how gut microbiota respond to antibiotic perturbation and the implications for public health.